Heat waves reveal additive genetic effects leading to sunburn resilience of grapevine berries - Heinekamp, Tom; Röckel, Franco; Herzog, Katja; Trapp, Oliver; Töpfer, Reinhard; Schwander, Florian (Frontiers in Plant Science, 2025)
Grape sunburn is an abiotic stress response induced under heat wave conditions. Heat stress is reaching new dimensions in terms of intensity and frequency in European cool-climate wine-growing regions. The damage to grape berries manifests in browning and shriveling, leading to yield loss and can reduce wine quality. Established management strategies like defoliation of the cluster zone in order to reduce fungal infection pressure could enhance this problem. Climate-adapted cultivars that are resilient to sunburn would resolve those trade-offs in vineyard management. In recent years, grapes grown in the Palatinate wine region of Germany have been affected by sunburn at an unprecedented rate. The intensity of sunburn damage in experimental fields located in this region was assessed for five years, taking advantage of the unexpectedly frequent heat waves in 2019, 2020, and 2022. Phenotyping of the grape sunburn symptoms was carried out in a segregating F1 mapping population of ‘Calardis Musqué’ x ‘Villard Blanc’ and a number of varieties. The population consists of 150 genotypes cultivated in two adjacent plots with four plants per F1-individual each, providing sufficient grape material for a reliable evaluation. Composite interval mapping (CIM) using a genetic map and 5 years of phenotypic field data of sunburn damage revealed two strong QTLs located on the lower arm of chromosome 11 with LODmax values of up to 16.3 and 26.1% of explained phenotypic variance and on chromosome 10 with a LODmax value of 10.3 and 14.1% of explained phenotypic variance. The highest sunburn resilience of berries was observed based on an additive effect of a specific allelic combination within both loci. QTL regions were screened for annotated and expressed genes in developing grape berries to provide a first insight into understanding possible principles of sunburn resilience. Some current fungus-resistant varieties (PIWIs), such as ‘Calardis Blanc’, have demonstrated resilience to sunburn. The reported QTLs open new possibilities to breed for grape sunburn resilient vines using marker-assisted selection (MAS), but also the challenges are discussed here. This knowledge could facilitate the planting of vineyards with fungus-resistant, sunburn-protected new varieties to ensure yield and wine quality while making viticulture more sustainable.